Parametric Study of an Organic Rankine Cycle Using Different Fluids - Touaibi, Rabah; Koten, Hasan; Boydak, Ozlem (Emerging Science Journal, 2020)
This work is an energy study of an organic Rankine cycle (ORC) for the recovery of thermal energy by comparing three organic fluids. This cycle is considered to be a promising cycle for the conversion of heat into mechanical energy suitable for low temperature heat sources; it uses more volatile organic fluids than water, which generally has high molecular weights, thus allowing operating pressures at temperatures lower than those of the traditional Rankine cycle. A thermodynamic model was developed using the Engineering Equation Solver (EES) software to determine its performance using different working fluids (toluene, R245fa and R123) under the same operating conditions, taking into account the effect of certain operating parameters and the selection of organic fluids on cycle performance. The results obtained show that the toluene organic fluid has the best thermal efficiency of the cycle compared to the other fluids; 14.38% for toluene, 13.68% for R123 and 13.19 for R245fa.